The Grammatical Aftermath of English Language Monolingualism in West Africa - Samuel Akanbi Babatunde (Journal of English Language and Education, 2026)
This study examines the English language grammatical aftermath among 400 English monolinguals in Ghana and Nigeria. Grounded in the communicative competence framework, the research investigates how exclusive reliance on English, coupled with the non-acquisition of indigenous languages, impacts grammatical competence. Using a quantitative survey design, data on Standard English concord and tense were collected via structured questionnaires and analyzed using descriptive statistics and t-tests. Findings reveal grammatical incompetence; fewer than 40% of respondents mastered complex subject–verb agreement constructions. Notably, background data indicate that 95% of participants possessed no indigenous language proficiency, confirming a state of total monolingualism. While statistically significant differences emerged between Ghanaian and Nigerian cohorts in tense (p = 0.005) and concord (p = 0.020), both groups exhibited uneven competence. The study concludes that monolingual dominance fails to guarantee solid English competence, leaving learners without functional communicative proficiency in either English or their indigenous languages.